2017
DOI: 10.1007/s10877-017-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

K-band Doppler radar for contact-less overnight sleep marker assessment: a pilot validation study

Abstract: An estimated 45 million persons in Europe are annually subjected to sleep-wake disorders. State-of-the-art polysomnography provides sophisticated insights into sleep (patho)physiology. A drawback of the method, however, is the obtrusive setting dependent on a clinical-based sleep laboratory with high operational costs. A contact-less prototype was developed to monitor limb movements and vital signs during sleep. A dual channel K-band Doppler radar transceiver captured limb movements and periodic chest wall mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Additionally, NRR is an attractive biomarker because it can be measured by many different sensors. Adherenceindependent strategies can be based on strain gauges placed under the bed (20), mattress sensors (21)(22)(23)(24), or ultrawideband radar systems (25,26). For highly engaged patients, there are many wearables and smartphone apps capable of measuring respiratory rates (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NRR is an attractive biomarker because it can be measured by many different sensors. Adherenceindependent strategies can be based on strain gauges placed under the bed (20), mattress sensors (21)(22)(23)(24), or ultrawideband radar systems (25,26). For highly engaged patients, there are many wearables and smartphone apps capable of measuring respiratory rates (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, many different studies have been put forward a few different radar types [4]- [7]. Radar noncontact measurements are performed in cases such as sleep apnea problem [8], [9], sudden infant death syndromes [10], elderly and patient home care [11], [12], detection of lives under the earthquake debris [13], through wall live detection [14], [15], and surveillance of the target [16]. The success of the studies is very promising for the future and it has been shown that in the cases the rate of intervention can be increased.…”
Section: Casesmentioning
confidence: 99%
“…The Doppler radar prototypes used in this study as well as the related signal processing have been described in detail in one of our earlier works [9].…”
Section: A Doppler Radarmentioning
confidence: 99%
“…Doppler radar has emerged as a promising technology for contact-less monitoring and assessment of physiological parameters. Contact-less estimation of respiration, limb movements as well as heart activity using Doppler radar have been demonstrated [8][9][10]. In this study, we aimed at: i) as a first step, assessing the feasibility of measuring arterial pulse waves at the femoral region using the Doppler radar technology, and consequently, ii) estimating the PTT between the heart-femoral regions as well as between the carotid-femoral regions using simultaneous Doppler radar measurements.…”
Section: Introductionmentioning
confidence: 99%